2022
DOI: 10.1038/s41598-022-09236-3
|View full text |Cite
|
Sign up to set email alerts
|

Altering the localization and toxicity of arsenic in rice grain

Abstract: Previous work has shown that inorganic As localizes in rice bran whereas DMA localizes in the endosperm, but less is known about co-localization of As and S species and how they are affected by growing conditions. We used high-resolution synchrotron X-ray fluorescence imaging to image As and S species in rice grain from plants grown to maturity in soil (field and pot) and hydroponically (DMA or arsenite dosed) at field-relevant As concentrations. In hydroponics, arsenite was localized in the ovular vascular tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The pro-ferroptotic effects reported upon zinc induction are strikingly similar to what has been reported in the case of arsenite. The trivalent inorganic form of arsenic is a highly toxic 1 group carcinogen [ 141 ]. Six-month-long exposure to arsenite in the concentration range of 0.5–5 mg/L drinking water mimicked the level of contamination in the natural environment and caused neuronal cell death and synaptic alterations throughout the hippocampus in mice.…”
Section: Poisons and Toxicantsmentioning
confidence: 99%
“…The pro-ferroptotic effects reported upon zinc induction are strikingly similar to what has been reported in the case of arsenite. The trivalent inorganic form of arsenic is a highly toxic 1 group carcinogen [ 141 ]. Six-month-long exposure to arsenite in the concentration range of 0.5–5 mg/L drinking water mimicked the level of contamination in the natural environment and caused neuronal cell death and synaptic alterations throughout the hippocampus in mice.…”
Section: Poisons and Toxicantsmentioning
confidence: 99%
“…All experiments were conducted under netting area to avoid pest disturbing to the growth of the plant. The matured paddy growth was ready to harvest after 100 days, and irrigation was stopped before 10 days of harvest [22].…”
Section: Pot Experimentsmentioning
confidence: 99%
“…Before digesting, the samples were stored in a chiller and kept under −20 • C to avoid drying. The extractions of grains were carried out by the wet method as described (AOAC 1984) [22]. Approximately 1.3-1.5 g of the extracted sections was weighed and placed in a conical flask and then supplemented with 15 mL of 69% concentrated nitric acid.…”
Section: Analysis Of Rice Grains Digests From the Pot Experimentsmentioning
confidence: 99%
“…Rice has been a particularly important sample in food safety assessments as many studies have shown it can accumulate and contain high levels of As. 13,31,32 Therefore, COLM-ICPMS was used to assess the As content in rice 13,17,18 and rice products. 11 To conrm the validity of COLM-ICPMS for use with rice samples, a rice our reference material was rst analysed by COLM-ICPMS.…”
Section: Colm-icpms For Food Safetymentioning
confidence: 99%